Long‐term follow up of nivolumab in previously untreated Japanese patients with advanced or recurrent malignant melanoma. Issue 6 (23rd May 2019) - Yamazaki, Naoya; Kiyohara, Yoshio; Uhara, Hisashi; Uehara, Jiro; Fujisawa, Yasuhiro; Takenouchi, Tatsuya; Otsuka, Masaki; Uchi, Hiroshi; Ihn, Hironobu; Hatsumichi, Masahiro; Minami, Hironobu
Abstract: The immune checkpoint inhibitor nivolumab inhibits the programmed death 1 receptor and suppresses the immune resistance of cancer cells. This is a long‐term follow up of a single‐arm, open‐label, multicenter, phase II study of nivolumab in untreated Japanese patients with stage III/IV or recurrent melanoma. In addition, a post–hoc subgroup analysis stratified by melanoma types was performed. Nivolumab was administered intravenously at a dose of 3 mg/kg every 2 weeks. The primary endpoint was the overall response rate (ORR), and secondary endpoints included overall survival (OS), progression‐free survival (PFS), best overall response, the disease control rate and change in tumor diameter. Safety was assessed by recording treatment‐related adverse events (TRAE), including select immune‐related adverse events. Of the 24 patients initially included in the primary phase II study, 10 survived for over 3 years (41.7%). The ORR was 34.8% (90% confidence interval [CI]: 20.8, 51.9) for all patients. When analyzing by melanoma type, the ORR was 66.7% (90% CI: 34.7, 88.3) for superficial spreading, 33.3% (90% CI: 11.7, 65.3) for mucosal, and 28.6% (90% CI: 10.0, 59.1) for acral lentiginous tumors. The median OS was 32.9 months, the 3‐year OS rate was 43.5%, and the 3‐year PFS rate was 17.2%. A long‐term response was observed in all the tumor types. The most common TRAE included skin toxicity (45.8%) and endocrine disorders (29.2%). This study demonstrated the long‐term efficacy and tolerability of nivolumab in patients with advanced or recurrent melanoma, irrespective of melanoma type. Abstract : We report the 3‐year follow‐up results from a previous phase II study of nivolumab in Japanese patients with unresectable stage III/IV or recurrent malignant melanoma who were previously untreated. Nivolumab (3 mg/kg every 2 weeks) resulted in the long‐term survival of patients with an overall response rate of 34.8% (90% CI: 20.8, 51.9; by melanoma type, ORR was greater in patients with superficial spreading melanoma [66.7%] compared with mucosal [33.3%] or acral lentiginous melanomas [28.6%]), and a median overall survival of 32.9 months. Our study demonstrated the long‐term efficacy and tolerability of nivolumab in patients with advanced or recurrent melanoma, irrespective of melanoma type.